Spiritual and religious perspectives in persons with visual impairment due to age-related macular degeneration - Salzer, Carina; Samoila, Lacramioara; Mortazavi Moshkenani, Hosnasadat; Samoila, Ovidiu (Frontiers in Psychology, 2023)
Age-related macular degeneration (AMD) is one of the global leading causes of severe vision loss. Patients suffering from AMD face complex spiritual and mental challenges that have an impact on the course of their disease, their quality of life and the relationship with their surroundings. A study was conducted through a 21-item questionnaire from August 2020 to June 2021, on 117 patients (from different countries), to investigate how patients' spirituality, religion, and their way of practicing them affect the experiences and daily lives of patients suffering from AMD as well as whether it helps them coping with the disease. Broadly translated, our study concludes that spirituality and religion are important factors that facilitate patients’ ability to cope with a progressive degenerative disease such as AMD. Patients who are religious are more at peace with having AMD. Elements that are contributing to patients being at peace which come with the acceptance of the disease, are prayer or meditation regularly. Spirituality and religion are important components that promote a healthier and happier emotional state and so mental well-being. Especially, by believing that death is not the end, patients are feeling more hopeful, which helps in their adjustment to a health condition that seems hopeless. An important number of AMD patients desire to talk about God with the medical staff. The profile of such a patient could be believing in a higher power, praying often, participating in religious services, being worried about the loss of vision, and needing assistance in daily life. An interdisciplinary and multidimensional approach of medical health professionals, mental health workers, and chaplains should be of great value.